Production of ink containing thermochromic dyestuff - AYDIN URUCU, OYA; BİRTANE, HATİCE (My University, 2022)
© 2022 Authors.Security inks are functional inks containing a binder and a special colorant used in money, checks and valuable documents. In security inks, thermochromic dyes, UV emitted, infrared emitted dyes can be used. Thermochromic dyestuffs provide different colors at different temperatures and ensure the requirements in the field of security. Thermochromic inks are generally used in smart packaging applications, high temperature alarms and security inks. Thermochromic dyes are generally metal-containing chemical materials. In this study, ink will be produced for metal surfaces by using commercial thermochromic dyestuff and it will be provided to act as a temperature warning plate. For this purpose, UV spectra of the thermochromic dyestuff was determinate with different temperature. Solvent-based ink with polyurethane binder containing 1; 3; 5% commercial thermochromic substance was produced. Screen prints were made on the metal surface with the produced ink. The color and gloss properties of the prints were measured with a spectrophotometer and glossmeter, respectively, at different temperatures. Print quality and surface properties were determined with an optical microscope. In addition, alkali, nitro, acid resistance tests were carried out. The reusability (color change) number was determined depending on how many temperature changes the print has. As a result, inks that change color at 38 °C with commercial thermochromic material were produced and successfully printed.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Computer Graphics and Computer-Aided Design; Physical Sciences; Computer Science Applications; printability; screen printing; security ink; UV –Viz. Spectroscopy